2017
DOI: 10.47678/cjhe.v47i2.186704
|View full text |Cite
|
Sign up to set email alerts
|

The Online Evaluation of Courses: Impact on Participation Rates and Evaluation Scores

Abstract: At one of Ontario’s largest universities, the University of Ottawa, course evaluations involve about 6,000 course sections and over 43,000 students every year. This paper-based format requires over 1,000,000 sheets of paper, 20,000 envelopes, and the support of dozens of administrative staff members. To examine the impact of a shift to an online system for the evaluation of courses, the following study sought to compare participation rates and evaluation scores of an online and paper-based course evaluation sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…Conversely, Burton et al (2012) found that when using online course evaluations, students' open-ended comments tended to be more positive overall. In contrast, Groen and Herry (2017) found no significant changes to the ratio of positive or negative responses. Two recent studies (Gakhal & Wilson, 2019;Holland, 2019) found that online course evaluations yielded dichotomous results.…”
Section: Presence Of Non-response Biascontrasting
confidence: 58%
See 1 more Smart Citation
“…Conversely, Burton et al (2012) found that when using online course evaluations, students' open-ended comments tended to be more positive overall. In contrast, Groen and Herry (2017) found no significant changes to the ratio of positive or negative responses. Two recent studies (Gakhal & Wilson, 2019;Holland, 2019) found that online course evaluations yielded dichotomous results.…”
Section: Presence Of Non-response Biascontrasting
confidence: 58%
“…Over time, however, faculty and administrators reported that paper-based survey collection was laborious with respect to aggregating and interpreting data (Crews & Curtis, 2011;Raman & Nedungadi, 2020). Consequently, in the early 2000s, colleges and universities began transitioning to online course evaluation collection methods (Groen & Herry, 2017). Some of the identified benefits of online systems included the ease and convenience of data collection, the depth of analysis permitted, and the prompt reporting of these methods (Gakhal & Wilson, 2019).…”
Section: Evolution Of Course Evaluationsmentioning
confidence: 99%